A 360° Video Surveillance Module for Forest Railway Tracks. Issue 2 (3rd July 2021) - Acharyya, Aritra
Abstract : The comprehensive theoretical model and detailed design of an omnidirectional video surveillance module have been presented in this paper; the said module possesses 360° horizontal field of view (FOV), and it is referred to as observer unit (OU). The OUs installed along the railway tracks passing through forest regions are capable of providing 24 × 7 h real-time video surveillance along the tracks and surrounding regions for avoiding wildlife-railway track accidents. The theoretical model and design have been validated via appropriate experimental measurements.